Sistem Pendaftaran Siswa Baru SMP Negeri 17 Lebong Berbasis Web Dengan Algoritma Sequential Searching - Yogi adindo; Yovi Apridiansyah; Ujang Juhardi; Dedy Abdullah (JUKOMIKA (Jurnal Ilmu Komputer dan Informatika), 2023)
Every year the process of accepting new students in various schools is a routine activity that must be carried out. It's just that each school applies its own way of accepting prospective new students. At SMP Negeri 17 Lebong, the registration process for new students is also still carried out independently, namely candidates come first to the school to see information and fill out forms in the school committee. The core purpose of this research is to build a new student registration system based on the website so that this website can be used to make it easier for prospective students to enroll at SMPN 17 Lebong. The results of research on the use of this system can also benefit the school in recording data on prospective new students through the website. In the development of this system using a sequential searching algorithm that functions to search for data that can facilitate the data collection process